Soil water dynamics, root systems, and plant responses in a semiarid grassland of Southern Patagonia - Ferrante, Daniela; Oliva, Gabriel Esteban; Fernández, Roberto J. (Elsevier, 2025)
Distribution of water enables different ecological niches and the coexistence of species. This separation may be in space: vertically in the soil profile or horizontally by lateral root exploration; and in time, as plants may use water at different periods. This study focused on the soil-plant water relation in semiarid Patagonia. Water potential at three depths: 10, 25 and 60 cm, and water content beneath vegetated and bare batches were measured. Access to water in the soil profile was studied in two grasses and a dwarf shrub based on the root biomass. Soil was usually dry at 10 cm ( 1.22 MPa 0.25) and 25 cm ( 1.00MPa 0.14) during summer. In dry years, it was also dry during autumn ( 1.17 MPa 0.32) at 10 cm depth). At 60-cm depth, soil was moist year-round ( 0.38 MPa 0.05). Soil conditions were not spatially homogeneous, as bare soil patches showed higher water content than vegetated patches. Dwarf shrubs presented both shallow and long roots, that extended laterally instead of exploring deep soil. It is hypothesized that this lateral expansion may give access to water under the bare soil patches, a resource that is not available to the other life forms.